Inter-Individual Responses to Experimental Muscle Pain: Baseline Physiological Parameters Do Not Determine Whether Muscle Sympathetic Nerve Activity Increases or Decreases During Pain - Kobuch, Sophie; Fazalbhoy, Azharuddin; Brown, Rachael; Macefield, Vaughan G. (Frontiers in Neuroscience, 2015)
We have previously reported that there are inter-individual differences in the cardiovascular responses to experimental muscle pain, which are consistent over time: intramuscular infusion of hypertonic saline, causing pain lasting ~60 minutes, increases muscle sympathetic nerve activity (MSNA) - as well as blood pressure and heart rate - in certain subjects, but decrease it in others. Here, we tested the hypothesis that baseline physiological parameters (resting MSNA, heart rate, blood pressure, heart rate variability) determine the cardiovascular responses to long-lasting muscle pain. MSNA was recorded from the common peroneal nerve, together with heart rate and blood pressure, during a 45-minute intramuscular infusion of hypertonic saline solution into the tibialis anterior of 50 awake human subjects (25 females and 25 males). Twenty-four subjects showed a sustained increase in mean amplitude of MSNA (160.9 ± 7.3 %), while 26 showed a sustained decrease (55.1 ± 3.5 %). Between the increasing and decreasing groups there were no differences in baseline MSNA (19.0 ± 1.5 vs 18.9 ± 1.2 bursts/min), mean BP (88.1 ± 5.2 vs 88.0 ± 3.8 mmHg), HR (74.7 ± 2.0 vs 72.8 ± 1.8 beats/min) or heart rate variability (LF/HF 1.8 ± 0.2 vs 2.2 ± 0.3). Furthermore, neither sex nor body mass index had any effect on whether MSNA increased or decreased during tonic muscle pain. We conclude that the measured baseline physiological parameters cannot account for the divergent sympathetic responses during tonic muscle pain